Is multivisceral resection in locally advanced gastrointestinal stromal tumours an acceptable strategy?. Issue 6 (25th May 2016) - Wong, Jolene Si Min; Tan, Grace Hwei Ching; Quek, Richard; Goh, Brian Kim Poh; Kwok, Li Lian; Kumar, Mrinal; Soo, Khee Chee; Teo, Melissa Ching Ching
Abstract : Background: Gastrointestinal stromal tumours (GISTs) represent the most common mesenchymal tumour of the gastrointestinal tract. Although the efficacy of targeted therapy cannot be over‐emphasized, surgery remains the only curative primary treatment for patients with localized disease. The median size of GIST at diagnosis is approximately 5–7 cm; however, it is not uncommon for tumours to be as large as 30–40 cm and involving multiple viscera. Methods: Data were retrospectively collected from patients with GISTs treated at the Singapore General Hospital and the National Cancer Centre Singapore over a 15‐year period. Standard resection of GIST without any additional organ removal was termed as a single organ resection (SOR). If the tumour was adjacent to another organ, necessitating the removal of more than one organ, the procedure was defined as a multivisceral resection (MVR). We aim to evaluate the role of MVR in the management of large GISTs. Results: A total of 187 patients underwent curative surgery for GIST between January 2000 and January 2014. Of the 187 patients, 40 (21%) underwent MVR whereas 147 (79%) had SOR. Patients in the MVR group had significantly larger tumour sizes ( P  < 0.001) yet R0 and R1 resection was achieved in all patients, and no intra‐peritoneal rupture was reported. On comparison of MVR versus SOR groups, there was no significant difference in in‐hospital morbidity and mortality. Conclusion: MVR may be required to achieve negative margins in patients with large GISTs, and can be performed with acceptable morbidity and mortality.